Mechanism of Fire Prevention with Liquid Carbon Dioxide and Application of Long-Distance Pressure-Holding Transportation Technology Based on Shallow Buried and Near-Horizontal Goaf Geological Conditions - Naifu Cao; Yuntao Liang (Journal of Chemistry)
Shallow burial, very close coal seam groups, and spontaneous combustion are typical characteristics of most coal seams in the Shendong mining area, China. With the continuous extension of the production level of various mines, some mining areas have gradually shown complex production conditions including multiple types of fire forms such as those in coal fields, small kilns, and multilayer mined-out and hidden high-temperature areas, resulting in fire control difficultly and posing threats to safety. With the aim of limiting the above problems, in this work, the liquid carbon dioxide fire prevention technology is focused on. Phase change and migration law of CO2 in the goaf are studied. Through the study on the influence of the use of liquid CO2 on the cooling law of high-temperature coal and on its spontaneous combustion characteristics and through thermal analysis experiments, it was observed that the porosity of loose coal has a significant impact on the cooling effect of carbon dioxide. Moreover, it was emphasized that the higher the CO2 concentration, the higher the rise in temperature of coal oxidation, and the increase of CO2 concentration was able to affect apparent activation of coal oxidation, leading to a theoretical basis to explain the effect of CO2 in inhibiting coal spontaneous combustion. The utilization of Fluent numerical modeling allowed us to simulate the diffusion radius of liquid CO2 injected into the goaf, to study the effective inerting radius of liquid CO2 on the left coal in the goaf. After comprehensive analysis of experiments and numerical simulations, appropriate equipment and process flow are selected and designed. Taking the Huojitujing well of Daliuta Coal Mine in Shendong mining area as the industrial test site, an intelligent pressure-holding transportation of liquid CO2 in the 1000 m transportation pipeline was developed. The surface liquid CO2 infusion capacity was 20 t/h, and the pressure-holding interval at the end of the transportation pipeline was determined to be 1.0–2.3 MPa. The maximum diffusion radius of the mined-out area is 300 m under the effect of positive air flow and self-expansion and diffusion of CO2 gas in the roadway. Under the influence of reverse wind flow and self-expansion and diffusion, the diffusion radius of the goaf is 150 m, and the maximum storage time of gaseous CO2 in the goaf is 27 h. Liquid CO2 was injected into the area with relevant presence of CO, an indicator of possible fires. Practice has proved that, after 65 hours and two perfusion processes, the CO concentration dropped from 790 ppm to 41 ppm, which indicates that liquid CO2 has a significant effect on fire prevention.